Physical Characteristic and Design Logics of Integrated Fast Reactor - HUO Xingkai, SONG Yingyun, MO Bu, FENG Wei, HU Yun (Yuanzineng kexue jishu)
To establish a highly efficient nuclear fuel cycle and make the most use of the uranium resource, the integrated fast reactor is a competitive option, featuring in its metal fuel and related pyro-processing. A metal-fueled core does not contain any low-atomic-number nuclides, resulting in less moderation and a harder spectrum of neutrons. With a harder spectrum, the metal-fueled core can benefit from a higher breeding ratio and deeper burnup, both of which are necessary for reducing the amount of spent fuel. However, the harder spectrum significantly increases the damage cross-section of structural material, due to which the burnup of the fuel is restricted by the accumulation of radiation damage of the cladding. The breeding ratio is also tightly related with the fissile nuclides enrichment; the higher the enrichment, the lower the breeding ratio; in this regards, to improve the breeding ratio the core should be loaded with larger amount of fuel and consequently lower enrichment, which can be easily realized by enlarging the fuel pin diameter. However, the larger pin diameter and higher amount of fuel loading are not economy in terms of fuel cost and subassembly manufacturing. To have a balance between the breeding ratio and fuel loading, the doubling time is a better and more comprehensive parameter. Normally, the fuel pin diameter is between 7.0 and 9.0 mm to accommodate both sides. Since a relatively higher internal breeding brings down the burnup reactivity loss, the core can be run with a low initial reactivity margin; it is not needed to load too much fuel at the beginning of one fuel cycle; as a result, the number of control rods can be decreased, beneficial to both the safety and economy aspects of the reactor. The metal fuel is also featured in its high thermal expansion coefficient, high heat conductivity and low operation temperature, all of which improve the passive safety of the core. In the presence of any sodium void born from overheating in abnormal conditions, the neutron moderation will decrease even more while the neutron spectrum goes much harder; these effects increase the effective fission neutron number of plutonium-239 and brings a positive reactivity. Although the sodium void reactivity is positive and has a large value in a metal-fueled core, compared with oxide-fueled core, the passive safety features mentioned above can provide enough negative feedback in the early stage of accidents, avoiding the overheating of the coolants and generation of the sodium void. Generally, the integrated fast reactor provides a desirable solution in the safe and efficient utilization of nuclear energy.